Terson's syndrome – Pathophysiologic considerations of an underestimated concomitant disease in aneurysmal subarachnoid hemorrhage. (November 2016) - Czorlich, Patrick; Skevas, Christos; Knospe, Volker; Vettorazzi, Eik; Westphal, Manfred; Regelsberger, Jan
Highlights: An elevated intracranial pressure (ICP) seems to be associated with a higher rate of Terson's syndrome. Terson's syndrome is a common disease in patients with subarachnoid hemorrhage. Genesis of Terson's syndrome seems to have different pathomechanism. Abstract: Terson syndrome (TS) is a common and underestimated concomitant disease in patients suffering from subarachnoid hemorrhage (SAH). Aim of this study was to evaluate the influence of an initial unconsciousness and raised intracranial pressure (ICP) on the development of TS. We performed a retrospective analysis of 213 prospective collected SAH patients screened for TS to investigate the impact of an initial unconsciousness and raised ICP on the development of TS. A univariate analysis followed by a multivariate logistic regression model was performed to identify risk factors that are associated with TS. The findings are all discussed and correlated with the present pathophysiologic considerations of TS. The rate of TS in this study was 23.9%. A higher risk of TS in the univariate analysis was associated with a Glasgow Coma scale ⩽ 7 (p = 0.001), higher Hunt and Hess grade (p = 0.001), Fisher grade IV (p = 0.002), intracerebral hemorrhage (p = 0.011), initial unconsciousness (p = 0.013) and an ICP of ⩾25 mmHg (p < 0.001). An ICP of ⩾25 mmHg was the only independent predictor for TS in the multivariate analysis (p = 0.007). TS patients had a higher mortality (p = 0.012) and a higher risk for a worse long-term outcome (p = 0.002). Notable that 5 of 51 TS patients (9.8%) in this study developed TS with no raised ICP or initial unconsciousness. Terson syndrome is a common concomitant disease in SAH patients. The pathomechanism leading to TS is not exclusively related to raised ICP levels and/or unconsciousness. However, these factors may be associated with a high percentage of TS.